Usefulness of Faecal Calprotectin Measurement in Children with Various Types of Inflammatory Bowel Disease. (14th May 2012) - Komraus, Marzena; Wos, Halina; Wiecek, Sabina; Kajor, Maciej; Grzybowska-Chlebowczyk, Urszula
Abstract : Introduction . The aim of the study was to assess the usefulness of the FC measurement in children with various types of IBD and relation to the disease activity. Patients and Methods . 91 patients (49 boys: 53.85% and 42 girls: 46.15%, mean age: 13.38 years, range 6–18 years) were included in the analysis. Patients were divided into the groups: B1—24 children with CD, B2—16 patients with UC, and a group comprising 31 children with other types of colitis; the control group (K) comprised 20 healthy children. FC was assayed by ELISA method, using Phical test (Calpro). Results . The mean faecal calprotectin concentrations were higher in children with CD and UC as compared to healthy controls, patients with eosinophilic, lymphocytic, and nonspecific colitis. A positive correlation was observed between FC concentrations and the disease activity (the PCDAI scale, the Truelove-Witts Scale, and the endoscopic Rachmilewitz Index). Conclusion . It seems that the FC concentrations can be a useful, safe, and noninvasive test in children suspected for IBD, since FC concentration is higher in children with CD and UC than in patients with other inflammatory diseases.